Sovereignty of the Paradigm âNon-validity of Isolated Traditionsâ over the Discourse of 5-7 Century ShÄ«âa Jurists - Ã™Â…Ã˜ÂµÃ˜Â·Ã™ÂÃ™ÂˆÃ›ÂŒ Ã™ÂÃ˜Â±Ã˜Â¯, Ã˜ÂÃ˜Â§Ã™Â…Ã˜Â¯; Ã˜Â·Ã˜Â¨Ã˜Â§Ã˜Â·Ã˜Â¨Ã˜Â§Ã›ÂŒÃ›ÂŒ Ã™Â¾Ã™ÂˆÃ˜Â±, Ã˜Â³Ã›ÂŒÃ˜Â¯ÃšÂ©Ã˜Â§Ã˜Â¸Ã™Â…; Ã˜Â±Ã˜Â¦Ã›ÂŒÃ˜Â³Ã›ÂŒÃ˜Â§Ã™Â†, Ã˜ÂºÃ™Â„Ã˜Â§Ã™Â…Ã˜Â±Ã˜Â¶Ã˜Â§ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Structuralists, including Thomas Kuhn, believe in the role of structures in knowledge production and view history of science as the history of periods totally torn apart. They believe that the criterion for any period of history of science is the emergence of a new paradigm, within which the scientific theories are developed. According to this approach, science development takes place within a specific chain, whose first link consists of pre-science (pseudo-science); the second link consists of function of conventional science; the third link consists of conventional science crisis; the fourth link consists of scientific evolution; and consequently the fifth link takes place as the incidence of new conventional science. Based on this model, the reason for the ShÄ«âa scholarsâ encounter with the isolated traditions can be evaluated in various periods of the history of Shiâism. For instance, the period from fifth to seventh century should be known as the age of the sovereignty of the paradigm of âprincipality of evidencesâ. This paradigm has had some opponents only in two stages, one at the beginning of its emergence (pre-science stage) and the other during its dissociation (conventional science crisis stage) and between these two stages we witness the indisputable sovereignty of âprincipality of evidencesâ and find no scholar who has believed in the validity of isolated traditions. Only then, with the scholarly activities of âAllÄma á¸¤illÄ« and his thought circle, a scientific revolution (change of paradigm) takes place and the paradigm of âprincipality of sanadâ prevails and dominates over the scholarly climate and maintains this domination until the appearance of traditionalism.